SARS-CoV-2: Operating room management strategies and recommendations - Zhang, Wen-jun; Zou, Fei-long; Hu, Dong-xia; Luo, Hong-liang; Wu, Li-dong; Hu, Jia-ling (Frontiers in Medicine, 2022)
Since the outbreak of SARS-COV-2/COVID19 in Wuhan, China in 2019, it has rapidly spread to the world, and the number of infections has gradually increased. The hospitalization rate of patients has also gradually increased, which poses a huge challenge to hospitals and medical staff for patients with SARS-COV-2 requiring surgical treatment. Therefore, avoiding cross-infection in the operating room is an important protective work. Operating room as an important department of the hospital, scientific and reasonable management is particularly important. Therefore, we have put forward corresponding suggestions and strategies for preoperative preparation and evaluation of patients, intraoperative management, postoperative terminal management, and protection of medical staff, and hope that these measures can better prevent and control the infection of SARS-COV-2 in the operating room.